2020
DOI: 10.1088/2053-1591/aba508
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Tribological and mechanical behaviour of AA6082—Graphene based composites with Ti particles

Abstract: In the recent years, high strength and low weight materials are being preferred in automobile sectors for fabricating high-speed rotating shafts and machineries. For satisfying dynamic requirements, Aluminium Metal Matrix Composites can be used. In this paper, an attempt has been made to fabricate AA 6082—graphene based Aluminium Matrix Composites reinforced with Titanium (Ti) particles. The effect of increase weight percentage of Graphene and Ti reinforcement on the mechanical characteristics was evaluated. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Due to the hindrance in dislocation movement, the surface hardness increased at a high concentration of reinforcements. Rajaganapathy et al (2020) also found that adding graphene into AA6082 aluminium-based composites could increase the graphene from 1% to 5%, gained from 86HV to 107HV with an increment of 24.08%. However, the hardness of the composites is improved by the existence of a comparatively more rigid reinforcement.…”
Section: Vickers Microhardness Testmentioning
confidence: 82%
“…Due to the hindrance in dislocation movement, the surface hardness increased at a high concentration of reinforcements. Rajaganapathy et al (2020) also found that adding graphene into AA6082 aluminium-based composites could increase the graphene from 1% to 5%, gained from 86HV to 107HV with an increment of 24.08%. However, the hardness of the composites is improved by the existence of a comparatively more rigid reinforcement.…”
Section: Vickers Microhardness Testmentioning
confidence: 82%
“…Then, 3% weight of Graphene and 3% weight of titanium particles were preheated to 500 °C and were manually introduced into the molten AA6082 and stirred continuously with the help of a mechanical stirrer to get a homogeneous mixture. 43 The molten mixture was then poured into a mold and was allowed to solidify at room temperature. After the solidification process, the Pin samples were removed from the mold and were machined in a lathe to a standard cylindrical specimen with a diameter of 10 mm and a length of 30 mm as per ASTM standards.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…Then, 3% weight of Graphene and 3% weight of titanium particles were preheated to 500 °C and were manually introduced into the molten AA6082 and stirred continuously with the help of a mechanical stirrer to get a homogeneous mixture. 43 The molten mixture was then poured into a mold and was allowed to solidify at room temperature.…”
Section: Preparations Of Ammc Pin Material-stir Casting Techniquesmentioning
confidence: 99%
“…The studies [34,[95][96][97][98] reported that the wear characteristics of the Al-based composites greatly rely on the class, geometry and architecture, and concentration of the reinforcing elements. In a statistical analysis of wear parameters, Suresh et al [99] stated that amongst all the wear parameters, wt% of reinforcement had the highest influence of around 29% on the wear properties of Al6063-based composites.…”
Section: Influence Of Particle Reinforcementmentioning
confidence: 99%